Yield contributing characters of BRRI dhan49 as influenced by integrated use of banana leaves with inorganic potassium fertilizer - Abdul Mannan, Md.; Abul Hashem, Md.; Sohanur Rahman, Md.; Uddin Talukder, fakhar; Kamrujjaman, Md. (International Journal of Advanced Geosciences, 2020)
A field experiment was carried out at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh during aman season of 2014 to study the integrated use of banana leaves with inorganic potassium fertilizer on the growth and yield of BRRI dhan49 following Randomized Complete Block Design (RCBD) with eight treatments and three replications. The highest plant height (85.55cm), panicle length (21.46cm), number of effective tillers hill-1 (11.54), number of filled grains panicle-1 (149.53), 1000-grain weight (21.85gm), grain yields (5.66 t ha-1) and straw yield (6.81 t ha-1) were obtained in the treatment T3 and the lowest plant height (77.10cm), panicle length (18.85cm), number of effective tillers hill-1 (8.64), number of filled grains panicle-1 (112.11), 1000-grain weight (19.96gm), grain yields (3.50 t ha-1) and straw yield (4.73 t ha-1) were recorded in the control. It can be recommended to integrated use of 50% K from banana leaves+50% K from MoP on growth and yield of BRRI dhan49.Â Â Â